simulasi,konfigurasi,jaringan PENINGKATAN KOMPETENSI JARINGAN KOMPUTER SISWA SMK TKJ MELALUI PELATIHAN KONFIGURASI JARINGAN BERBASIS SIMULASI PADA SMK PAB 8 SAMPALI - Wirhan Fahrozi; Nidia Enjelita Saragih; Elida Tuti Siregar; Linda Wahyuni (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This activity aims to improve the computer network competency of Vocational High School (SMK) students majoring in Computer and Network Engineering (TKJ) through simulation-based network configuration training. The methods used include partner needs analysis, preparation of training materials and modules, implementation of training using network simulation software, and evaluation of participants' understanding and skills through observation and discussion. A simulation-based approach was applied to overcome the limitations of physical practice devices and increase learning effectiveness. The results of the activity showed that the training was able to improve students' understanding of computer network concepts and their ability to perform basic network configuration independently. Students also showed increased confidence and readiness in facing network practices in school and the workplace. Thus, simulation-based network configuration training can be an effective learning alternative in supporting the improvement of SMK TKJ students' competency.